The Effect Of Family Social Support On Anxiety In Facing The Workplace In Fresh Graduates - Haura Luthfiyyani; Lilis Ratnasari (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Entering the workforce is a challenge fresh graduates face after graduating from college. Rising unemployment and increasingly fierce competition contribute to anxiety in fresh graduates, making social support from family, as their closest relatives, essential. This study aims to examine the effect of family social support on anxiety in facing the workplace in fresh graduate students. This study used a quantitative method with a purposive sampling technique and involved 124 respondents: fresh graduate students aged 21–25, graduated less than six months ago, and had no work experience. The results showed a significance value of 0.000 (p<0.010), with a contribution of 24,5%. Based on these results, the hypothesis is accepted: there is a very significant effect of family social support on anxiety in facing the world of work in fresh graduate students.